Gerakan Literasi Sains melalui Pengenalan STEAM pada Anak di Komunitas Ã¢â‚¬Å“Panggon MocoÃ¢â‚¬Â Gresik - Sumarno, Wahyu Kyestiati; Shodikin, Ali; Rahmawati, Adinda Aulia; Shafira, Putri Dian; Solikha, ImroÃ¢â‚¬â„¢atus (Jurnal Pemberdayaan Masyarakat, 2021)
Scientific literacy is one of the important literacies that children need to have. However, there are many findings that show the low level of scientific literacy in Indonesian children. "Panggon Moco" is one of the reading park communities (TBM) which was formed due to the community’s concern for the success of the literacy program. Until now, the literacy developed by this community is still limited to reading literacy. Therefore, it is necessary to develop other literacy such as scientific literacy. To answer this challenge, it is necessary to carry out a scientific literacy activities for children in the Panggon Moco community. A learning approach that has been proven to improve scientific literacy in children is STEAM (science, technology, engineering, art, and mathematics). The method of implementing this program includes several activities, namely (1) discussion and equalization of perceptions; (2) making Fun STEAM Lab books; (3) the STEAM experiment; and (4) STEAM literacy assistance. This activity is carried out offline and online. The results obtained from this program are increasing children's understanding of STEAM and increasing students' interest and motivation in learning.